Social learning for designing and scaling out sustainable land-use systems in conflict-affected areas - Bonatti, Michelle; Medina, Leonardo; Rodríguez, Tatiana; Rio Duque, Martha Lilia del; Morales Muñoz, Héctor; Eufemia, Luca; Chavez-Miguel, Giovanna; Lana, Marcos A.; Löhr, Katharina; Vanegas Cubillos, Martha Cristina; Chará, Julián; Sieber, Stefan; et al. (2022)
This Policy Brief provides scientifically sound guidance for decision-makers to help promote social learning in policy instruments and to foster synergies and address trade-offs among the multiple objectives of sustainable land use systems